Evaluation of T315I mutation frequency in chronic myeloid leukemia patients after imatinib resistance. (1st May 2013) - Chahardouli, Bahram; Zaker, Farhad; Mousavi, Seied Asadollah; Kazemi, Ahmad; Ostadali, Mohammadreza; Nadali, Fatemeh; Rostami, Shahrbano; Alimoghaddam, Kamran; Ghavamzade, Ardeshir
Abstract : The occurrence of resistance mutations in the Abl kinase domain plays a central role in drug treatment failure in chronic myeloid leukemia (CML) patients. Among them, the T315I mutation at the gatekeeper position affects a common Abl kinase contact residue and confers complete resistance to all known ATP-competitive BCR-ABL inhibitors. In the present study, an allele-specific oligonucleotide reverse transcriptase polymerase chain reaction assay was used to detect T315I mutation in a cohort of 60 imatinib-resistant CML patients. In terms of disease phase, 43 patients (71%) were in late chronic phase, 4 (7%) in accelerated phase, and 13 (22%) in blastic phase. The prevalence of the T315I mutation was found to be 7% (4/60). All four patients with mutation were in advance phases and had previously lost all their responses. The results of the study confirmed that this method is low cost and easy tool to operate for T315I mutation screening and direct sequencing should be performed in positive cases for confirmation.